2008
DOI: 10.3171/jns/2008/109/8/0238
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic deep brain stimulation after anesthetic inhalation in Parkinson disease: a preliminary study

Abstract: The authors found that MER can be adequately performed while the patient receives a desflurane anesthetic, and the results can serve as a guide for STN electrode implantation. This may be a good alternative surgical method in patients with PD who are unable to tolerate deep brain stimulation surgery with local anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 24 publications
3
64
1
1
Order By: Relevance
“…The availability of this surgical technique provides patients unwilling or unable to tolerate awake surgery with an alternative option for DBS lead placement. Previous studies on asleep DBS lead placement with the use of intraoperative imaging have indicated that this may be an appropriate surgical technique, but only a limited number have evaluated the postoperative clinical outcomes in a quantitative fashion [6,8,10,12,13,14,15,16]. This study retrospectively compares the efficacy of STN DBS for PD in two groups of patients at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of this surgical technique provides patients unwilling or unable to tolerate awake surgery with an alternative option for DBS lead placement. Previous studies on asleep DBS lead placement with the use of intraoperative imaging have indicated that this may be an appropriate surgical technique, but only a limited number have evaluated the postoperative clinical outcomes in a quantitative fashion [6,8,10,12,13,14,15,16]. This study retrospectively compares the efficacy of STN DBS for PD in two groups of patients at a single institution.…”
Section: Introductionmentioning
confidence: 99%
“…A critical limitation in our understanding of anesthetic best practices is that only a few studies have quantified the effect of anesthetics on MER [14,41,44,45], although a number have qualitatively assayed it, suggesting that too much sedation degrades the MER quality [13,14,15,20,39,41,42,43,44,46,47,48,49,50,51,52,53,54]. Considering those studies that quantified the effects on MER, we do know that some were affected by anesthetic choice, for example, during propofol sedation, background population activity within the STN, as well as FR, was reduced [13,14,41,43,44,51], REMI combined with ketamine demonstrated a reduction in background activity with preserved neuronal FRs [45], and REMI alone had no effect [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, PD patients with obvious "off-medication" symptoms of anxiety, painful dystonia, and respiratory distress may not be good candidates for the lengthy tolerating the surgical procedures while awake [54][55][56][57]. In this section, we will report our own experience with general anesthesia during DBS surgery with MER and compare it with data from awake procedures (see Table 3).…”
Section: Anesthetic Considerations In Dbs: Awake Versus General Anestmentioning
confidence: 99%
“…It also is popular in neurosurgery because it can allow early extubation and facilitate early neurological evaluation [70][71]. MER also can be performed well at an anesthetic level of 0.8±0.2 minimum alveolar concentration (MAC) [54].…”
Section: The Effect Of the Anesthetic Agent Desfluranementioning
confidence: 99%
See 1 more Smart Citation